2008
DOI: 10.1007/s00125-008-1224-4
|View full text |Cite
|
Sign up to set email alerts
|

High-dose thiamine therapy for patients with type 2 diabetes and microalbuminuria: a randomised, double-blind placebo-controlled pilot study

Abstract: Pakistan Higher Education Commission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 9 publications
2
124
2
1
Order By: Relevance
“…High-dose therapy with thiamine and the thiamine monophosphate (TMP) derivative benfotiamine prevented the development of microvascular complications in experimental diabetes [3][4][5]. A pilot-scale trial of type 2 diabetic patients with incipient nephropathy (microalbuminuria) showed that high-dose thiamine therapy improved renal function and induced regression of microalbuminuria [6,7]. Further understanding of how thiamine supplementation prevents incipient nephropathy and other microvascular complications is now required.…”
Section: Introductionmentioning
confidence: 99%
“…High-dose therapy with thiamine and the thiamine monophosphate (TMP) derivative benfotiamine prevented the development of microvascular complications in experimental diabetes [3][4][5]. A pilot-scale trial of type 2 diabetic patients with incipient nephropathy (microalbuminuria) showed that high-dose thiamine therapy improved renal function and induced regression of microalbuminuria [6,7]. Further understanding of how thiamine supplementation prevents incipient nephropathy and other microvascular complications is now required.…”
Section: Introductionmentioning
confidence: 99%
“…For survival of these patients insulin is not necessary.In these patients obesity is a major cause of insulin resistance while increase age and physical inactivity are also important factors.Ketoacidosis occur because of stress of other infection. it has strong genetic predisposition (Riaz, S. 2009). …”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…While prevalence of hypertension in type 2 diabetic patients is estimated at 50% with one estimated as high as 74%. (Riaz, S et al 2009) …”
Section: Prevalence Of Diabetic Hypertensive Nephropthymentioning
confidence: 99%
“…The application of benfotiamine and the resulting activation of the enzyme transketolase in the diabetic, hyperglycemic system can also produce beneficial effects on general nerve health. Benfotiamine has been shown in many preclinical [21,[31][32][33][34][35][36][37][38][39][40][41][42][43] as well as clinical studies [44][45][46][47][48][49][50][51][52][53][54][55][56][57] to prevent the formation of AGEs [21,53] and eventually with continued treatment to reverse the symptoms associated with the neuropathy [46,47,52,57]. By increasing intracellular levels of thiamine, benfotiamine indirectly induces enzymatic and biochemical pathways [58][59][60] through elevated concentrations of thiamine diphosphate resulting in a reduced level of damaging glucose-derived chemical protein species [21,22,32,[37][38][39][60][61]…”
Section: Introductionmentioning
confidence: 99%